Forgotten Surgical Sponge Mimicking Fat Necrosis Following Breast Reduction Surgery - Sandra Scharfetter, MD; Laurenz Weitgasser, MD; Florian Wimmer, MD; Barbara Ebner, MD; Elisabeth Russe, MD; Gottfried Wechselberger, MD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. A forgotten surgical sponge following surgery, also called textiloma, is a rare yet significant issue, whereas fat necrosis is more prevalent, particularly in breast surgery. We present a case experiencing persistent postoperative pain, a lump in the right breast, delayed wound healing, and the formation of a fistula following breast reduction surgery. The patient's symptoms were managed conservatively for 1 year because they were initially misdiagnosed as fat necrosis. A subsequent mammogram suggested a retained surgical sponge. The diagnosis of a textiloma was verified during surgical intervention. This case highlights the significance of implementing intraoperative preventive measures, including the meticulous counting of surgical sponges. Additionally, it emphasizes the importance of reassessing patients with unresolved symptoms.